IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA PT. BANK INTERNASIONAL INDONESIA TBK (STUDI KASUS: BANK BII CABANG UTAMA SURABAYA) - PRASETYO, ANDI (Jurnal Akuntansi AKUNESA, 2013)
This research aims to know how the implementation of Good Corporate Governance (GCG)in Surabaya Branch of Bank BII. Samples taking technique done by purposivesampling.Sample research is all the ranks of leaders in Surabaya Branch of Bank BII whichincludes twelve people, that will ensure the implementation of GCG in SurabayaBranch ofBank BII. The analytical method used is descriptive method with percentage.From theseresults, showing that the level of implementation of GCG in the Surabaya Main Branch ofBank BII at 94,07% which means has implemented the principles of GCG very well.Keywords: Good Corporate Governance